Short circuit currents - Schlabbach, J. (Jürgen) (London, United Kingdom Institution of Engineering and Technology, 2005)
The following topics are dealt with: Calculation of impedance of electrical equipment; calculation of short-circuit current in AC three-phase HV-systems; influence of neutral earthing on single-phase short-circuit currents; calculation of short-circuit currents in low-voltage systems; double earth-fault and short-circuit currents through earth; factors for the calculation of short-circuit currents; calculation of short-circuit currents in DC auxiliary installations; effects of short-circuit currents; limitation of short-circuit currents; special problems related to short-circuit currents; and data of equipment.
Electronic reproduction.
Keywords: Short circuits -- Mathematical models; Electronic books